Characterization of the Burnout syndrome and chronic work stress in instructors at the Financial Services Training Centre – SENA - Berbeo Rodríguez, Ana María
This paper gives an overview of the most relevant findings on the features of Burnout Syndrome (occupational burnout) and job stress among the instructors from the Financial Services Training Centre, by identifying the factors that may have greater relevance and impact on the psychosocial risk within the labour environment, to propose alternatives for the prevention and improvement in the quality of life and development of activities of instructors. The featuring was based on the principles of Schaufeli, Leiter, Maslach and Jackson Kyriacou, Winnubst and Golembiewski among others, where the following are identified as variables that affect this psychosocial risk: EE: Emotional Exhaustion, (D): Depersonalization and PA: Personal Accomplishment. An assessment tool based on the method of Maslach (MBI-Ed) (Maslach, C. and Jackson, S.E. 1981; 1986) (Seisdedos, 1997) was administered and features of the participants such as age, gender, marital status, profession, type of contract, area where they work, seniority, working day and position were taken into account.